Synthesis, characterization, spectroscopic and electrochemical properties of phthalocyanines substituted with four 3-ferrocenyl-7-oxycoumarin moieties - ÖZKAYA, ALİ RIZA (ELSEVIER SCIENCE SA, 2011)
The synthesis, spectroscopic and electrochemical properties of the tetra-(3-ferrocenyl-7-oxycoumarin)substituted zinc (II) and cobalt (II) phthalocyanines (3 and 4) are reported for the first time. The synthesis of novel 3-ferrocenyl-7-hydroxycoumarin (1) was performed according to Perkin reaction, and the ligand, 7-(3,4-dicyanophenoxy)-3-ferrocenylcoumarin (2), was synthesized by the reaction of 3-ferrocenyl-7-hydroxycoumarin with 4-nitrophthalonitrile in the presence of K(2)CO(3) as the base in dry dimethylformamide. The preparation of the corresponding zinc (II) and cobalt (II) metallo phthalocyanines (3 and 4) substituted with 3-ferrocenyl-7-oxycoumarin moieties at beta-positions of the phthalocyanine ring was achieved by the cyclotetramerization of the coumarin ligand (2) with relevant metal(II) acetates in dry 2-dimethylaminoethanol. The new compounds have been characterized by elemental analyses, FT-IR, (1)H NMR, Mass and electronic spectroscopy. The fluorescence property of the zinc metallo phthalocyanine (3) is strongly affected by the presence of ferrocenyl moiety. The ferrocenyl moieties were very efficient in quenching the excited state of 3, which show very poor fluorescent intensity. The electrochemical properties of the complexes were also investigated by cyclic and differential pulse voltammetry techniques in non-aqueous medium. It was found that the redox-active ferrocene substituents are reduced concurrently at one potential. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Coumarin (2H-1-benzopyran-2-one); Ferrocene; Fluorescence; Electrochemistry; METAL-FREE; PHOTOPHYSICAL BEHAVIOR; COUMARIN SUBSTITUENTS; FLUORESCENCE; DERIVATIVES; COMPLEXES; FERROCENE; STATE; CROWN; 4-METHYLUMBELLIFERONE